Safety of mineral salt containing potassium and magnesium as a novel food pursuant to Regulation (EU) 2015/2283 - EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA); Dominique Turck; Torsten Bohn; Montaña Cámara; Jacqueline Castenmiller; Stefaan De Henauw; Ángeles Jos; Helle Katrine Knutsen; Alexandre Maciuk; Inge Mangelsdorf; Breige McNulty; Harry J. McArdle; et al. (EFSA Journal)
Abstract Following a request from the European Commission, the EFSA Panel on Nutrition, Novel Foods and Food Allergens (NDA) was asked to deliver an opinion on a mineral salt, containing potassium and magnesium, as a novel food (NF) pursuant to Regulation (EU) 2015/2283. The NF is a mineral salt that consists mainly of magnesium potassium trichloride hexahydrate. The information provided on the composition is sufficient for characterising the NF and does not raise safety concerns. The production process is sufficiently described and does not raise safety concerns. The NF is intended to be added to meat, sausages and dishes based on pasta, rice and other cereals. Taking into account the composition of the NF and the proposed use and use levels, the Panel considers that the consumption of the NF is not nutritionally disadvantageous. Regarding the presence of bromide in the NF, the Panel notes that the combined daily intake of bromide from the NF and the background diet does not exceed the tolerable daily intake of bromide of 0.4 mg/kg body weight (bw) per day. Based on its physicochemical characteristics and solubility data, the NF is expected to be dissociated in the gastrointestinal tract. Taking into account the composition and the nature of the NF, the Panel considers that no toxicological studies with the NF are required. The Panel concludes that the NF (i.e. a mineral salt containing potassium and magnesium) is safe under the proposed conditions of use.